Weather, ambient air pollution and bronchial asthma in Athens, Greece - Nastos, Panagiotis Th (Seasonal forecasts, climatic change and human health, 2008)
The associations between various meteorological parameters, concentrations of PM10, SO2, and O3 pollutants and bronchial asthma of residents of the wider region of Athens are examined in this study. For this purpose, 1,288 patients’ admissions (412 males and 876 females) recorded in 13 pneumonological clinics of Sotiria Hospital, which is the major Hospital for respiratory diseases in Athens, were analyzed for the period 1/1/2001–31/12/2002. The meteorological data were available by the National Observatory of Athens and the concentrations of PM10, SO2, and O3 pollutants were obtained by the air pollution network of 10 stations of the Ministry of Environment (Directorate of Air and Noise pollution Control). The evaluation of the possible relationship between the bronchial asthma admissions (BAA) and the meteorological variables was achieved by the application of Generalized Linear Models with Poisson distribution, because the medical dataset presents large divergence from a Gaussian distribution. The results showed that a statistically significant (p < 0.01) negative correlation between all examined air temperature variables, water vapor pressure, evaporation, sunshine, total solar irradiance, and BAA exists. Moreover, the findings of the analysis showed that a statistically significant relationship between the examined pollutants and BAA on the same day does not exist, with the exception of O3, which is correlated negatively (p < 0.01) with BAA. Nevertheless, there is a statistically significant lag effect (7–8 days) between the increase in BAA and the peak in the concentrations of PM10, SO2, and O3 pollutants. During the cold period of the year (October–April), BAA is significantly associated with O3 lag 2 day. The interannual variation of bronchial asthma admissions (BAA) reveals peaks within the transitional seasons of the year (spring and autumn), while the main minimum is apparent during summer period and especially in August.